Effectiveness of Learner Facilitation Plan on the Learning Outcomes of Secondary Class Students - Banu, Zehra (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
A research project on the title “Effectiveness of the learner facilitation plan on the learning outcomes of secondary students in science” was undertaken in which an innovative pedagogical practice of; learner facilitation plan (LFP) designed by Vidya Bhawan G S T college was used during the practice teachoing session od B.Ed. Students in the session 2016. Under the research project for a period of 15 days the secondary class was taught using the LFP and the learning outcomes of thee students was evaluated. A single group pre-test, post test experimentation was carried out, data as collected using a self-made achievement test and a set of 15 lesson plans on various topics of science were prepared on the LFP and used as a treatment plan. The findings suggested a great rise in the learning outcomes of the secondary students pointing towards the great potential of the LFP in raising the learning outcomes of the secondary students